Does Taxpayer Supervision Affect Compliance and Tax Revenue? Evidence from Indonesia - Tambunan, Frederik Halomoan; Kuncoro, Antonius Ragil (Journal of Applied Accounting and Taxation, 2026)
Taxpayer supervision is one of the key strategies employed by the Directorate General of Taxes to ensure taxpayer compliance and optimize tax revenue. Motivated by questions regarding the effectiveness of this strategy, this study aims to analyze the impact of three types of supervisory activities—Requests for Clarification of Data and/or Information (P2DK), Field Data Collection (KPDL), and Issuance of Tax Collection Letters (STP)—on tax revenue and tax compliance, as well as to examine the mediating role of tax compliance. The novelty of this study lies in the use of a quantitative, panel data approach at the national level, integrating all three forms of tax supervision as independent variables. The quantitative approach analysis is based on panel data from 259 selected Tax Service Offices (KPP) in Indonesia for the period 2021–2023, obtained through purposive sampling. The results show that P2DK has a significant positive effect on both tax revenue and compliance, while STP only affects tax revenue. In contrast, KPDL does not exhibit a significant influence on either. Furthermore, tax compliance significantly increases revenue but does not mediate the relationship between the supervisory activities and tax revenue. These findings suggest that P2DK is the most effective supervisory instrument for simultaneously enhancing tax revenue and compliance. These findings suggest that P2DK is the most effective tool for simultaneously enhancing compliance and optimizing revenue. Policy implications include prioritizing P2DK in supervision strategies, improving the quality and follow-up of KPDL data, and adopting the approaches used in P2DK for both STP issuance and KPDL procedures.